Novel Optimization Method of Active Frequency Multiplier Utilizing Harmonic Terminating Impedances with DGS - Kutin, Petr; Kasal, Miroslav (Radioengineering Society, 2006)
A novel method for the optimization of the active frequency multiplier utilizing the harmonic terminating impedances with the defected ground structures (DGS) has been developed. Furthermore, a new type of the low-pass filter with DGS for the higher harmonic suppression will be reported. Experimental conversion gains (14.52 dB for the doubler, 5.56 dB for the tripler and 0.43 dB for the quadrupler) and real power-added efficiency (32.76 % for the doubler, 10.15 % for the tripler and 1.42 % for the quadrupler) have been attained. To our knowledge, in the considered frequency range, these results represent the best performance reported up to date for the active frequency multipliers utilizing the low-cost BJTs.
Keywords: Frequency multiplier; defected ground structure; DGS; harmonic terminating; low-pass filter; optimi-zation